The problem of fraud detection in telecommunication networks on the base of intelligent technologies - Kupershtein, L. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Basic methods and facilities of the fraud management systems realization in telecommunication networks are considered. Fraud management systems realization on the base of neuro-fuzzy networks is proposed. Hardware part realization of neural-fuzzy fraud management system is proposed as a neurocomputer based on programmable logic gate array